(untitled) (Journal of the Medical College for Women & Hospital, 2025)
Globally, traditional and complementary medicine (T&CM) plays a vibrant role in healthcare, whether as a primary or supplementary service. Its use is growing all over, though often underestimated. Traditional medicine (TM) is a long-standing practice based on cultural knowledge, skills, and beliefs, used for maintaining health and treating physical and mental illnesses. Complementary and alternative medicine (CAM) includes practices outside conventional care, while T&CM combines CAM and TM, encompassing related products, practices, and providers. Traditional, indigenous, and ancestral knowledge has sustained health for millennia and is still crucial in many parts of the world. World Health Organization (WHO) mentions that 170 of 194 member states use practices like herbal medicine, acupuncture, yoga, and indigenous therapies. WHO’s 13th General Program of Work (2019-2023) aims to advance Sustainable Development Goal 3 by reaching 3 billion more people through universal health coverage, better emergency response, and healthier populations. T&CM can support this goal by becoming part of essential health services, expanding access to safe, effective, and culturally appropriate care to meet community needs and strengthen primary healthcare systems. J Med Coll Women Hosp.2025; 21 (1):10-12